A High-Sensitivity Fiber Biosensor Based on PVDF-Excited Surface Plasmon Resonance in the Terahertz Band - Yani Zhang; Yiming Yao; Zhe Guang; Jia Xue; Qiuyang Wang; Jiaqin Gong; Zohaib Ali; Zhongtian Yang (Photonics, 2023)
In this paper, a D-type photonic crystal fiber (PCF) with Zeonex material as the substrate and polyvinylidene fluoride (PVDF) material as the surface plasmon resonance (SPR) excitation layer is proposed for biosensing in the terahertz (THz) band. Analyzed with a finite element method, the proposed biosensor has shown excellent sensing properties for analyte refractive indices ranging from 1.32 to 1.45. With a maximum sensor resolution of 8.40 × 10−7 refractive index unit (RIU) and a figure of merit of 39.42 RIU−1, the maximum wavelength sensitivity and amplitude sensitivity can reach 335.00 μm/RIU and −66.01 RIU−1, respectively. A ±2% fabrication tolerance analysis is also performed on the biosensor to prove its practical feasibility. We conclude that our proposed PCF biosensor utilizing PVDF-excited SPR can provide high sensitivity, and thus a compact, label-free, and convenient solution for biomedical liquid sensing in the THz band.